Value at Risk Estimation of Portfolio Affected by the BDS Movement: A Copula Approach - Binarvian Sofawi; Dhoriva Urwatul Wutsqa (Indonesian Journal of Applied Statistics, 2026)
This study aims to estimate value at risk (VaR) as a measure of the maximum potential loss in an investment portfolio through the application of a Copula approach to stocks affected by the Boycott, Divestment, and Sanctions (BDS) Movement. The data used are the daily return data of MAPI from PT Mitra Adiperkasa, Tbk, FAST from PT Fast Food Indonesia, Tbk, and UNVR from PT Unilever Indonesia, Tbk obtained from the closing stock prices. The returns used are daily simple returns from March 1, 2019, to February 29, 2024, consisting of 1,130 days. The model used in this study is the ARMA-GARCH Copula model. Autoregressive moving average (ARMA) is used due to the involvement of time influence in estimation, while generalized autoregressive conditional heteroskedasticity (GARCH) is used to address the high volatility in stocks. The selection of the best copula model using maximum likelihood estimation (MLE) involves five copulas: gaussian copula, t-Student copula, Clayton copula, Frank copula, and Gumbel copula. The results of the analysis show that Clayton copula is the best model, with VaR of the portfolio of stocks affected by the Boycott, Divestment, and Sanctions (BDS) movement at the 99%, 95%, and 90% confidence levels are 3.45%, 2.11%, and 1.55%, respectively. These findings suggest that lower tail dependence plays an important role in portfolio risk, indicating the potential for simultaneous extreme losses. Therefore, investors are encouraged to consider copula-based risk measurement methods and diversification strategies to minimize potential portfolio losses.Keywords: ARMA, copula, GARCH, returns, value at risk